Sustainable community development and corporate social investments by a platinum mining company in South Africa - Motaung, Lelentle (University of the Witwatersrand, Johannesburg, 2024)
South African mining companies implement corporate social investment (CSI) projects meant to benefit host communities by addressing various development needs. However, constant conflicts arise between these communities and mining companies despite these CSI projects. Using a qualitative case study approach, this study sought to understand reasons for the persistence of this conflict. The study applied the Ladder of Citizen Participation (Arnstein, 1969) in analysing the design and implementation of CSI programmes of one platinum mining company in South Africa. Findings suggest that existing conflicts reflect a dissonance between the mining company’s CSI objectives and community development needs, illustrated by the poor quality of engagement with local communities in determining CSI priorities. Specifically, inferior quality community consultations, lack of communication about forums for consultation and poor community representation in consultation processes hinder successful prioritisation of community needs in CSI objectives. In addition, the mining company seems to always act in its own interest by prioritising exclusionary elitism in its community engagement strategies. This, coupled with a lack of regular monitoring and evaluation, leads to misalignment between the CSI and sustainable community development objectives, and impedes the successful implementation of CSI initiatives.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of African Philanthropy to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Participation; Community Engagement; Sustainable Community Development; UCTD; SDG-8: Decent work and economic growth